Inorganic / organic composite carrier type Ziegler-Natta catalyst and preparation method thereof
By using inorganic/organic composite support structure in Ziegler-Natta catalyst, modifying the silica pores and increasing the active center spacing, the polyethylene chain entanglement problem caused by the catalyst is solved, and the low entanglement preparation of high molecular weight polyethylene is achieved , reduces production costs and improves processing performance.
Patent Information
- Application Number
- CN202411269934.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2024-12-13
AI Technical Summary
During the polymerization process, the existing Ziegler-Natta catalysts have severe tangles of polyethylene chains due to random and tight distribution of active centers, which affects mechanical properties and processing difficulty. The methods to reduce the entanglement density have problems such as increased production costs and reduced performance.
Using inorganic/organic composite support type Ziegler-Natta catalyst, the silica pores are modified through cyanolated polystyrene, which increases the active center spacing and reduces chain overlap. Metallocene compounds such as cyclopentadienyl titanium trichloride are used. and alkyl magnesium chloride cocatalysts to form core-shell structures to improve catalytic activity and stability.
It effectively reduces the degree of entanglement of primary ecological polyethylene chain segments, improves the molecular weight and morphological regularity of the polymer, reduces production costs and improves processing performance.
Smart Images

Figure BDA0005038405520000141 
Figure BDA0005038405520000151
Abstract
Description
Technical Field
[0001] The invention relates to the field of olefin catalysts, and in particular to an inorganic / organic composite carrier type Ziegler-Natta catalyst and a preparation method thereof. Background Art
[0002] Ultra-high molecular weight polyethylene (UHMWPE) is high-density polyethylene with a molecular weight of at least one million. Its development began in the 1960s. It is one of the most resilient plastics with excellent mechanical properties. It is widely used in transportation, textiles, mining, agriculture, and chemical industries. UHMWPE also has good physiological inertness. As a material for artificial joints and orthopedic parts, it has great applications in clinical medicine.
[0003] Since the molecular weight of ultra-high molecular weight polyethylene is much larger than that of ordinary polyethylene products, it is difficult to process and synthesize, and there are a lot of physical entanglements between and within its ultra-long polyethylene chains, which greatly restricts the movement and relaxation behavior of the polyethylene chains, increases its melt viscosity, and leads to processing difficulties. The mechanical properties are also affected by chain entanglement. Compared with entangled UHMWPE, low-entanglement UHMWPE has a stronger chain segment diffusion ability, and can obtain products with low molding defects and excellent mechanical properties. The way to reduce the entanglement density of nascent UHMWPE is mainly through the preparation of low-entanglement nascent powder based on catalyst technology, blending modification to reduce the degree of entanglement, and the use of solvents and force fields to disentangle during downstream processing. Although the regulation of chain entanglement can be achieved in the blending or processing links, there are still many industrial problems such as increased production costs, increased processing difficulty, and reduced product performance. Therefore, the preparation technology of nascent low-entanglement UHMWPE is crucial, and the core is catalyst technology.
[0004] In industry, ultra-high molecular weight polyethylene often needs to be produced by a slurry polymerization process using a supported catalyst. The supported catalyst can avoid scaling of the reactor wall during the polymerization process and obtain UHMWPE primary particles with good morphology and high bulk density. Commercial UHMWPE is mostly produced using a supported Ziegler-Natta (ZN) catalyst, but the pores of the catalyst are prone to bimetallic deactivation due to the random distribution and close arrangement of active centers, and the polymerization activity is not high enough. What is more disadvantageous is that the closely distributed active centers make the growing active chains very close to each other, which easily forms chain entanglements. Therefore, how to improve the Ziegler-Natta catalyst to prepare low-entanglement polyethylene has become a new problem to be solved. Summary of the invention
[0005] The purpose of the present invention is to provide an inorganic / organic composite carrier type Ziegler-Natta catalyst and a preparation method thereof, which solves the problem of how to modify the Ziegler-Natta catalyst to prepare low-entanglement polyethylene.
[0006] The present invention is achieved through the following technical solutions:
[0007] In one aspect, the present invention provides an inorganic / organic composite carrier type Ziegler-Natta catalyst, the Ziegler-Natta catalyst comprising: an inorganic / organic composite carrier and a metallocene compound and a co-catalyst supported on the inorganic / organic composite carrier;
[0008] The doping amount of the metallocene compound is 0.01wt% to 2wt% of the Ziegler-Natta catalyst;
[0009] The inorganic / organic composite carrier has silicon dioxide as a core and is wrapped with an outer shell formed by cyanated polystyrene.
[0010] Furthermore, in the inorganic / organic composite support type Ziegler-Natta catalyst, the preparation of the inorganic / organic composite support includes:
[0011] Dissolving cyanated polystyrene in tetrahydrofuran solvent to prepare a 1wt% to 4wt% polystyrene solution;
[0012] Completely immerse the activated silica in the polystyrene solution and let it stand for 20 to 30 hours;
[0013] Adding the silicon dioxide after standing to the polystyrene solution in a mass ratio of silicon dioxide to polystyrene of 1:(1-3), stirring and mixing at 0°C to obtain the mixed solution;
[0014] The isopentane is heated to 35-50° C. and then added into the mixed solution. The isopentane is evaporated by heating at a rate of 1-3 mL / min, and then washed and dried to obtain the inorganic / organic composite carrier.
[0015] Furthermore, in the inorganic / organic composite support type Ziegler-Natta catalyst, the preparation of the cyanated polystyrene comprises:
[0016] Dissolving styrene and divinylbenzene in a benzoyl peroxide solution, adding triallyl isocyanate, hexadecanol, polyvinyl alcohol and SDS-PEG solution and mixing evenly to obtain a mixed solution; wherein the molar ratio of styrene, divinylbenzene and triallyl isocyanate is 1:(0.5-0.8):(0.5-0.8); the molar ratio of triallyl isocyanate, hexadecanol, polyvinyl alcohol and SDS-PEG solution is 1:(0.1-0.4):(3-5):(0.01-0.1);
[0017] The obtained mixed solution is reacted at a temperature of 40° C. to 55° C. for 5 h to 10 h, and then the temperature is raised to 60° C. to 75° C. for 5 h to 7 h to obtain the cyanated polystyrene.
[0018] Furthermore, in the inorganic / organic composite carrier type Ziegler-Natta catalyst, the mass ratio of SDS to PEG4000 in the SDS-PEG solution is (1-2):1;
[0019] And / or, the mass content of the SDS-PEG solution is 1wt% to 10wt%.
[0020] Further, in the inorganic / organic composite support type Ziegler-Natta catalyst, the average pore size of the inorganic / organic composite support is 50nm to 80nm;
[0021] And / or, the average diameter of the inorganic / organic composite carrier is 20 μm to 35 μm.
[0022] Further, in the inorganic / organic composite supported Ziegler-Natta catalyst, the metallocene compound is selected from: one or more of cyclopentadienyl titanium trichloride, bis(cyclopentadienyl) titanium trichloride, bis(cyclopentadienyl) zirconium dichloride, bis(pentamethylcyclopentadienyl) zirconium dichloride, bis(cyclopentadienyl) dimethyl titanium, bis(cyclopentadienyl) diphenyl titanium, pentamethylcyclopentadienyl titanium trichloride, pentaethylcyclopentadienyl titanium trichloride, bis(1,2-dimethylcyclopentadienyl) diphenyl titanium and bis(1,2-diethylcyclopentadienyl) diphenyl titanium.
[0023] Further, in the inorganic / organic composite carrier type Ziegler-Natta catalyst, the doping amount of the co-catalyst is 10wt% to 20wt% of the Ziegler-Natta catalyst, and the co-catalyst includes alkyl magnesium chloride and aluminoxane;
[0024] Preferably, the aluminoxane is selected from: methylaluminoxane and / or tetrabutylaluminoxane;
[0025] Preferably, the alkyl magnesium chloride is selected from one or more of methyl magnesium chloride, ethyl magnesium chloride and butyl magnesium chloride.
[0026] On the other hand, the present invention also provides a method for preparing the inorganic / organic composite carrier type Ziegler-Natta catalyst, comprising:
[0027] Adding the inorganic / organic composite carrier and alkyl magnesium chloride into a tetrahydrofuran solvent containing alcohol, and stirring to obtain an alcohol adsorption carrier;
[0028] The metallocene compound and aluminoxane are added to a tetrahydrofuran solvent containing alcohol, mixed with an alcohol adsorption carrier, and stirred to obtain a catalyst carrier;
[0029] A tetrahydrofuran solvent containing titanium tetrachloride and an alkane solvent are added to the catalyst carrier, and the Ziegler-Natta catalyst is obtained after stirring and drying.
[0030] Furthermore, in the preparation method of the inorganic / organic composite carrier type Ziegler-Natta catalyst, the alcohol is selected from: one or more of ethanol, propanol, 1-butanol, ethylene glycol, propylene glycol, and 1,4-butanediol.
[0031] Furthermore, in the preparation method of the inorganic / organic composite carrier type Ziegler-Natta catalyst, the alkane solvent is selected from one or more of n-hexane, isohexane, n-heptane, 2-methylhexane, 3-methylhexane, n-octane, 2-methylheptane, and 3-methylheptane.
[0032] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0033] In the inorganic / organic composite carrier type Ziegler-Natta catalyst provided by the present invention, an inorganic / organic composite carrier with a core-shell structure is used, and the pores of silica are modified by cyanated polystyrene, so that the polymerization activity is released smoothly and the entanglement degree of the nascent polyethylene chain segments is reduced; and the cyanated polystyrene has a certain steric hindrance, which effectively separates the active sites, increases the distance between active centers, and inhibits the occurrence of chain overlap during the polymerization process, thereby reducing the entanglement degree of the nascent polyethylene molecular chains. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with Examples. The illustrative embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0035] At present, the production of commercial UHMWPE mainly uses ZieglerNatta (ZN) catalysts, but ZN catalysts have many active sites and high polymerization temperatures. The polyethylene (PE) molecular chains formed by polymerization are very easy to form topological entanglements, thereby inhibiting the mobility of the polymer chains and ultimately affecting the mechanical and processing properties. In ZN catalysts, the active sites are randomly distributed on the carrier surface and are close to each other. During the polymerization process, the polymer chain segments grown on adjacent active sites overlap a lot, resulting in molecular chain entanglement. This is because in the early stage of polymerization, the active center is in an exothermic state, and the possibility of chain growth nucleation is higher than the possibility of chain crystallization. The primary chain segments overlap in the chain to form chain entanglements. Afterwards, the chain segments fold in an entangled state and gradually form crystals. After the formation of the crystal nucleus, the nucleation barrier from the exothermic active center decreases, and the temperature from the active center to the chain end gradually decreases. At this time, the crystal growth rate increases. As the chain folds, crystals are continuously generated around the active center, and the ethylene diffusion rate continues to decrease. At this time, the chain crystallization rate is greater than the chain growth rate, and the entanglement density of the polymer chain segments gradually decreases. Therefore, during the polymerization process, the entanglement density gradually decreases from the chain end to the active center and is heterogeneously distributed along the polymer chain segment. Based on the formation of chain entanglements, the way to reduce the entanglement density of nascent UHMWPE is mainly achieved by preparing low-entanglement nascent powder based on catalyst technology, blending modification to reduce the degree of entanglement, and using solvents and force fields to disentangle during downstream processing. Although the regulation of chain entanglement can be achieved in the blending or processing link, there are still many industrial problems such as increased production costs, increased processing difficulty, and reduced product performance. Therefore, the present invention provides an inorganic / organic composite carrier-type Ziegler-Natta catalyst to solve the current entanglement problem of nascent UHMWPE.
[0036] In one aspect, the present invention provides an inorganic / organic composite carrier type Ziegler-Natta catalyst, the Ziegler-Natta catalyst comprising: an inorganic / organic composite carrier and a metallocene compound and a co-catalyst supported on the inorganic / organic composite carrier;
[0037] The doping amount of the metallocene compound is 0.01wt% to 2wt% of the Ziegler-Natta catalyst; it can be 0.01wt%, 0.03wt%, 0.05wt%, 0.08wt%, 0.1wt%, 0.3wt%, 0.5wt%, 0.8wt%, 1wt%, 1.3wt%, 1.5wt%, 1.8wt%, 2wt%, etc., but is not limited to the listed values, and other values not listed within the range are also applicable;
[0038] The inorganic / organic composite carrier has silicon dioxide as a core and is wrapped with an outer shell formed by cyanated polystyrene.
[0039] In the inorganic / organic composite carrier-type Ziegler-Natta catalyst provided by the present invention, cyanated polystyrene modifies the pores of silica, and the swelling behavior of the cyanated polystyrene leads to an increase in the mass transfer resistance of ethylene during polymerization, so that the polymerization activity is released smoothly, and the entanglement degree of the nascent polyethylene chain segments is reduced; the cyanated polystyrene has a certain steric hindrance, which effectively separates the active sites, increases the distance between active centers, and inhibits the occurrence of chain overlap during the polymerization process, thereby reducing the entanglement degree of the nascent polyethylene molecular chains.
[0040] In the inorganic / organic composite carrier type Ziegler-Natta catalyst provided by the present invention, the inorganic / organic composite carrier provided has a core-shell structure, with silicon dioxide as the core, improving the stability of the metallocene activated material on the carrier, reducing the probability of bimolecular deactivation and β-hydrogen elimination during the polymerization reaction, thereby improving the molecular weight of the polymer, and obtaining a polyolefin with a regular morphology and high apparent density. With cyanated polystyrene as the shell, the cyanation of the polystyrene microspheres has an electron-withdrawing induction effect, can reduce the electron cloud density around the transition metal Ti, improve Lewis acidity, weaken β-H elimination reaction, can effectively increase the exposure ratio of the active site, increase the monomer coordination reaction time, is conducive to the insertion of olefin monomers, and improves the catalytic activity and polymer molecular weight.
[0041] Furthermore, the preparation of the inorganic / organic composite carrier includes:
[0042] Dissolving cyanated polystyrene in tetrahydrofuran solvent to prepare a 1wt% to 4wt% polystyrene solution;
[0043] Completely immerse the activated silica in the polystyrene solution and let it stand for 20 to 30 hours;
[0044] Adding the silicon dioxide after standing to the polystyrene solution in a mass ratio of silicon dioxide to polystyrene of 1:(1-3), stirring and mixing at 0°C to obtain the mixed solution;
[0045] The isopentane is heated to 35-50° C. and then added into the mixed solution. The isopentane is evaporated by heating at a rate of 1-3 mL / min, and then washed and dried to obtain the inorganic / organic composite carrier.
[0046] Further, the preparation of the cyanated polystyrene comprises:
[0047] Dissolving styrene and divinylbenzene in a benzoyl peroxide solution, adding triallyl isocyanate, hexadecanol, polyvinyl alcohol and SDS-PEG solution and mixing evenly to obtain a mixed solution; wherein the molar ratio of styrene, divinylbenzene and triallyl isocyanate is 1:(0.5-0.8):(0.5-0.8); the molar ratio of triallyl isocyanate, hexadecanol, polyvinyl alcohol and SDS-PEG solution is 1:(0.1-0.4):(3-5):(0.01-0.1);
[0048] The obtained mixed solution is reacted at a temperature of 40° C. to 55° C. for 5 h to 10 h, and then the temperature is raised to 60° C. to 75° C. for 5 h to 7 h to obtain the cyanated polystyrene.
[0049] Furthermore, the mass ratio of SDS to PEG4000 in the SDS-PEG solution is (1-2):1;
[0050] And / or, the mass content of the SDS-PEG solution is 1wt% to 10wt%, which can be 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, etc., but is not limited to the listed values, and other values not listed within the range are also applicable. .
[0051] Furthermore, the average pore size of the inorganic / organic composite carrier is 50nm to 80nm;
[0052] And / or, the average diameter of the inorganic / organic composite carrier is 20 μm to 35 μm.
[0053] Further, the metallocene compound is selected from: one or more of cyclopentadienyl titanium trichloride, bis(cyclopentadienyl) titanium trichloride, bis(cyclopentadienyl) zirconium dichloride, bis(pentamethylcyclopentadienyl) zirconium dichloride, bis(cyclopentadienyl) dimethyl titanium, bis(cyclopentadienyl) diphenyl titanium, pentamethylcyclopentadienyl titanium trichloride, pentaethylcyclopentadienyl titanium trichloride, bis(1,2-dimethylcyclopentadienyl) diphenyl titanium and bis(1,2-diethylcyclopentadienyl) diphenyl titanium.
[0054] Further, the doping amount of the promoter is 10wt% to 20wt% of the Ziegler-Natta catalyst, and can be 10wt%, 11wt%, 13wt%, 15wt%, 17wt%, 19wt%, 20wt%, etc., but is not limited to the listed values, and other values not listed within the range are also applicable;
[0055] The cocatalyst includes alkyl magnesium chloride and aluminoxane;
[0056] Preferably, the aluminoxane is selected from: methylaluminoxane and / or tetrabutylaluminoxane;
[0057] Preferably, the alkyl magnesium chloride is selected from one or more of methyl magnesium chloride, ethyl magnesium chloride and butyl magnesium chloride.
[0058] On the other hand, the present invention also provides a method for preparing the inorganic / organic composite carrier type Ziegler-Natta catalyst, comprising:
[0059] Adding the inorganic / organic composite carrier and alkyl magnesium chloride into a tetrahydrofuran solvent containing alcohol, and stirring to obtain an alcohol adsorption carrier;
[0060] The metallocene compound and aluminoxane are added to a tetrahydrofuran solvent containing alcohol, mixed with an alcohol adsorption carrier, and stirred to obtain a catalyst carrier;
[0061] A tetrahydrofuran solvent containing titanium tetrachloride and an alkane solvent are added to the catalyst carrier, and the Ziegler-Natta catalyst is obtained after stirring and drying.
[0062] Further, the alcohol is selected from: one or more of ethanol, propanol, 1-butanol, ethylene glycol, propylene glycol, and 1,4-butanediol;
[0063] Preferably, the alkane solvent is selected from one or more of n-hexane, isohexane, n-heptane, 2-methylhexane, 3-methylhexane, n-octane, 2-methylheptane and 3-methylheptane.
[0064] In order to further illustrate the present invention, an inorganic / organic composite support type Ziegler-Natta catalyst and a preparation method thereof provided by the present invention are described below in combination with examples. However, it should be understood that these examples are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and specific operating processes are given only to further illustrate the features and advantages of the present invention, rather than to limit the claims of the present invention, and the protection scope of the present invention is not limited to the following examples.
[0065] In the following implementation, the metallocene compound is selected from cyclopentadienyltitanium trichloride; the aluminoxane is selected from methylaluminoxane; the alkylmagnesium chloride is selected from methylmagnesium chloride; the alcohol is selected from ethanol; and the alkane solvent is selected from n-hexane.
[0066] Embodiment 1:
[0067] The inorganic / organic composite carrier type Ziegler-Natta catalyst of this embodiment includes: an inorganic / organic composite carrier and a metallocene compound and a co-catalyst supported on the inorganic / organic composite carrier; the doping amount of the metallocene compound is 0.01wt% of the Ziegler-Natta catalyst; the doping amount of the co-catalyst is 10wt% of the Ziegler-Natta catalyst.
[0068] Wherein, the preparation of the inorganic / organic composite carrier includes:
[0069] (1) dissolving styrene and divinylbenzene in a benzoyl peroxide solution, adding triallyl isocyanate, hexadecanol, polyvinyl alcohol and SDS-PEG solution and mixing them evenly to obtain a mixed solution; wherein the molar ratio of styrene, divinylbenzene and triallyl isocyanate is 1:0.5:0.5; the molar ratio of triallyl isocyanate, hexadecanol, polyvinyl alcohol and SDS-PEG solution is 1:0.1:3:0.01; the mass ratio of SDS and PEG4000 in the SDS-PEG solution is 1:1; and the mass content of the SDS-PEG solution is 1wt%;
[0070] (2) reacting the obtained mixed solution at 40° C. for 5 h, and then heating it to 60° C. for 5 h to obtain cyanated polystyrene;
[0071] (3) dissolving the cyanated polystyrene in tetrahydrofuran solvent to prepare a 1 wt % polystyrene solution;
[0072] (4) completely immersing the activated silica into the polystyrene solution and leaving it to stand for 20 hours;
[0073] (5) adding the silica after standing to the polystyrene solution in a mass ratio of 1:1, stirring and mixing at 0° C. to obtain the mixed solution;
[0074] (6) isopentane is heated to 35° C. and then added to the mixed solution. The isopentane is evaporated by heating at a rate of 1 mL / min, and then washed and dried to obtain the inorganic / organic composite carrier.
[0075] The preparation of the inorganic / organic composite carrier type Ziegler-Natta catalyst of this embodiment includes:
[0076] (1) adding an inorganic / organic composite carrier and an alkyl magnesium chloride into a tetrahydrofuran solvent containing an alcohol, and stirring to obtain an alcohol adsorption carrier;
[0077] (2) adding the metallocene compound and aluminoxane to a tetrahydrofuran solvent containing an alcohol, mixing with an alcohol adsorption carrier, and stirring to obtain a catalyst carrier;
[0078] (3) Adding a tetrahydrofuran solvent containing titanium tetrachloride and an alkane solvent to the catalyst carrier, stirring and drying to obtain the Ziegler-Natta catalyst.
[0079] The average pore size of the inorganic / organic composite carrier obtained in this embodiment is 50 nm to 80 nm, and the average diameter is 20 μm to 35 μm.
[0080] Embodiment 2:
[0081] The inorganic / organic composite carrier type Ziegler-Natta catalyst of this embodiment includes: an inorganic / organic composite carrier and a metallocene compound and a co-catalyst loaded on the inorganic / organic composite carrier; the doping amount of the metallocene compound is 0.1wt% of the Ziegler-Natta catalyst; the doping amount of the co-catalyst is 13wt% of the Ziegler-Natta catalyst.
[0082] Wherein, the preparation of the inorganic / organic composite carrier includes:
[0083] (1) dissolving styrene and divinylbenzene in a benzoyl peroxide solution, adding triallyl isocyanate, hexadecanol, polyvinyl alcohol and SDS-PEG solution and mixing them evenly to obtain a mixed solution; wherein the molar ratio of styrene, divinylbenzene and triallyl isocyanate is 1:0.6:0.75; the molar ratio of triallyl isocyanate, hexadecanol, polyvinyl alcohol and SDS-PEG solution is 1:0.2:4:0.05; the mass ratio of SDS and PEG4000 in the SDS-PEG solution is 1.5:1; and the mass content of the SDS-PEG solution is 6wt%;
[0084] (2) reacting the obtained mixed solution at 48° C. for 8 h, and then heating it to 65° C. for 6 h to obtain cyanated polystyrene;
[0085] (3) dissolving the cyanated polystyrene in tetrahydrofuran solvent to prepare a 2 wt % polystyrene solution;
[0086] (4) completely immersing the activated silica in the polystyrene solution and leaving it to stand for 24 hours;
[0087] (5) adding the silica after standing to the polystyrene solution in a mass ratio of silica to polystyrene of 1:2, stirring and mixing at 0° C. to obtain the mixed solution;
[0088] (6) isopentane is heated to 45° C. and then added to the mixed solution. The isopentane is evaporated by heating at a rate of 2 mL / min, and then washed and dried to obtain the inorganic / organic composite carrier.
[0089] The preparation method of the inorganic / organic composite support type Ziegler-Natta catalyst in this embodiment is consistent with that in Example 1.
[0090] The average pore size of the inorganic / organic composite carrier obtained in this embodiment is 50 nm to 80 nm, and the average diameter is 20 μm to 35 μm.
[0091] Embodiment 3:
[0092] The inorganic / organic composite carrier type Ziegler-Natta catalyst of this embodiment includes: an inorganic / organic composite carrier and a metallocene compound and a co-catalyst loaded on the inorganic / organic composite carrier; the doping amount of the metallocene compound is 0.5wt% of the Ziegler-Natta catalyst; the doping amount of the co-catalyst is 15wt% of the Ziegler-Natta catalyst.
[0093] Wherein, the preparation of the inorganic / organic composite carrier includes:
[0094] (1) dissolving styrene and divinylbenzene in a benzoyl peroxide solution, adding triallyl isocyanate, hexadecanol, polyvinyl alcohol and SDS-PEG solution and mixing them evenly to obtain a mixed solution; wherein the molar ratio of styrene, divinylbenzene and triallyl isocyanate is 1:0.8:0.8; the molar ratio of triallyl isocyanate, hexadecanol, polyvinyl alcohol and SDS-PEG solution is 1:0.4:5:0.1; the mass ratio of SDS and PEG4000 in the SDS-PEG solution is 2:1; and the mass content of the SDS-PEG solution is 10wt%;
[0095] (2) reacting the obtained mixed solution at 55° C. for 10 h, raising the temperature to 75° C. for 7 h, and obtaining cyanated polystyrene;
[0096] (3) dissolving the cyanated polystyrene in tetrahydrofuran solvent to prepare a 4 wt % polystyrene solution;
[0097] (4) completely immersing the activated silica into the polystyrene solution and leaving it to stand for 30 hours;
[0098] (5) adding the silica after standing to the polystyrene solution in a mass ratio of silica to polystyrene of 1:3, stirring and mixing at 0° C. to obtain the mixed solution;
[0099] (6) isopentane is heated to 50° C. and then added to the mixed solution. The isopentane is evaporated by heating at a rate of 3 mL / min, and then washed and dried to obtain the inorganic / organic composite carrier.
[0100] The preparation method of the inorganic / organic composite support type Ziegler-Natta catalyst in this embodiment is consistent with that in Example 1.
[0101] The average pore size of the inorganic / organic composite carrier obtained in this embodiment is 50 nm to 80 nm, and the average diameter is 20 μm to 35 μm.
[0102] Embodiment 4:
[0103] The preparation method of the inorganic / organic composite support type Ziegler-Natta catalyst of this embodiment is consistent with that of Example 3, except that the doping amounts of the metallocene compound and the co-catalyst in the Ziegler-Natta catalyst are different.
[0104] The inorganic / organic composite carrier type Ziegler-Natta catalyst of this embodiment includes: an inorganic / organic composite carrier and a metallocene compound and a co-catalyst loaded on the inorganic / organic composite carrier; the doping amount of the metallocene compound is 1wt% of the Ziegler-Natta catalyst; the doping amount of the co-catalyst is 17wt% of the Ziegler-Natta catalyst.
[0105] The average pore size of the inorganic / organic composite carrier obtained in this embodiment is 50 nm to 80 nm, and the average diameter is 20 μm to 35 μm.
[0106] Embodiment 5:
[0107] The preparation method of the inorganic / organic composite support type Ziegler-Natta catalyst of this embodiment is consistent with that of Example 3, except that the doping amounts of the metallocene compound and the co-catalyst in the Ziegler-Natta catalyst are different.
[0108] The inorganic / organic composite carrier type Ziegler-Natta catalyst of this embodiment includes: an inorganic / organic composite carrier and a metallocene compound and a co-catalyst loaded on the inorganic / organic composite carrier; the doping amount of the metallocene compound is 2wt% of the Ziegler-Natta catalyst; the doping amount of the co-catalyst is 20wt% of the Ziegler-Natta catalyst.
[0109] The average pore size of the inorganic / organic composite carrier obtained in this embodiment is 50 nm to 80 nm, and the average diameter is 20 μm to 35 μm.
[0110] Comparative Example 1
[0111] The preparation of the Ziegler-Natta catalyst of this comparative example is based on the preparation method of the Ziegler-Natta catalyst provided in Example 3, except that the inorganic / organic composite carrier is replaced with silicon dioxide, that is, pure silicon dioxide is used as the carrier.
[0112] Comparative Example 2
[0113] The preparation of the Ziegler-Natta catalyst of this comparative example is based on the preparation method of the Ziegler-Natta catalyst provided in Example 3, except that the inorganic / organic composite carrier is replaced by a silica / polystyrene composite carrier, wherein the polystyrene is not cyanated.
[0114] Test Case
[0115] The Ziegler-Natta catalysts prepared in Examples 1-5 and Comparative Examples 1-2 were mixed with triethylaluminum co-catalyst to obtain a catalyst composition having an aluminum / titanium molar ratio of 75:1, and the catalyst composition was subjected to polymerization reaction with purified ethylene. The polymerization temperature was controlled at 95°C ± 5°C, the pressure was 3.0 MPa ± 0.3 MPa, the gas flow rate was controlled at 0.8 m / s ± 0.2 m / s, and the residence time was 1 h.
[0116] The polymer material is discharged into the slurry reactor, and the polymerization reaction is continued in the presence of a solvent, the polymerization temperature is controlled at 90°C ± 5°C, the pressure is 0.6MPa ± 0.1MPa, the material residence time is 70min, and the material level is controlled at 55% ± 5%;
[0117] The discharged powder is degassed and dried to remove unreacted monomers, and then treated with nitrogen containing a small amount of water vapor to finally obtain high molecular weight polyethylene powder.
[0118] The entanglement degree of the nascent polyethylene sample was tested by HAAKE MARSⅢ rheometer. The polyethylene sample was pressed for 30 minutes at 130℃ and 20MPa using a hot press to obtain a small disc with a diameter of 20mm and a thickness of 2mm. The rheological test process was carried out under nitrogen protection to avoid sample oxidation. A dynamic time scan test was used to observe the entanglement degree of the nascent UHMWPE at 10rad·s -1 , 0.5% strain condition. The ratio of initial elastic modulus to equilibrium elastic modulus GNt (t=0) is used as an indicator to measure the degree of entanglement. The ethylene polymerization activity of the catalyst, the weight average molecular weight and molecular weight distribution index of the obtained polyethylene are tested, and the results are shown in Table 1.
[0119] Table 1
[0120]
[0121]
[0122] It can be seen from the results in Table 1 that the Ziegler-Natta catalyst prepared in the embodiment of the present invention can obtain polyethylene with low entanglement degree and higher molecular weight on catalytic ethylene, while maintaining a narrow molecular weight distribution.
[0123] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. An inorganic / organic composite carrier type Ziegler-Natta catalyst, characterized in that: The Ziegler-Natta catalyst comprises: an inorganic / organic composite carrier and a metallocene compound and a co-catalyst supported on the inorganic / organic composite carrier; The doping amount of the metallocene compound is 0.01wt% to 2wt% of the Ziegler-Natta catalyst; The inorganic / organic composite carrier has silicon dioxide as a core and is wrapped with an outer shell formed by cyanated polystyrene.
2. The inorganic / organic composite support type Ziegler-Natta catalyst according to claim 1, characterized in that: The preparation of the inorganic / organic composite carrier comprises: Dissolving cyanated polystyrene in tetrahydrofuran solvent to prepare a 1wt% to 4wt% polystyrene solution; The activated silicon dioxide is completely immersed in the polystyrene solution and allowed to stand for 20 to 30 hours; Adding the silicon dioxide after standing to the polystyrene solution in a mass ratio of silicon dioxide to polystyrene of 1:(1-3), stirring and mixing at 0°C to obtain the mixed solution; The isopentane is heated to 35-50° C. and then added into the mixed solution. The isopentane is evaporated by heating at a rate of 1-3 mL / min, and then washed and dried to obtain the inorganic / organic composite carrier.
3. The inorganic / organic composite supported Ziegler-Natta catalyst according to claim 2, characterized in that: The preparation of the cyanated polystyrene comprises: Dissolving styrene and divinylbenzene in a benzoyl peroxide solution, adding triallyl isocyanate, hexadecanol, polyvinyl alcohol and SDS-PEG solution and mixing evenly to obtain a mixed solution; wherein the molar ratio of styrene, divinylbenzene and triallyl isocyanate is 1:(0.5-0.8):(0.5-0.8); the molar ratio of triallyl isocyanate, hexadecanol, polyvinyl alcohol and SDS-PEG solution is 1:(0.1-0.4):(3-5):(0.01-0.1); The obtained mixed solution is reacted at a temperature of 40° C. to 55° C. for 5 h to 10 h, and then the temperature is raised to 60° C. to 75° C. for 5 h to 7 h to obtain the cyanated polystyrene.
4. The inorganic / organic composite supported Ziegler-Natta catalyst according to claim 3, characterized in that: The mass ratio of SDS to PEG4000 in the SDS-PEG solution is (1-2):1; And / or, the mass content of the SDS-PEG solution is 1wt% to 10wt%.
5. The inorganic / organic composite supported Ziegler-Natta catalyst according to claim 1 or 2, characterized in that: The average pore size of the inorganic / organic composite carrier is 50nm to 80nm; And / or, the average diameter of the inorganic / organic composite carrier is 20 μm to 35 μm.
6. The inorganic / organic composite supported Ziegler-Natta catalyst according to claim 1, characterized in that: The metallocene compound is selected from the group consisting of: cyclopentadienyl titanium trichloride, bis(cyclopentadienyl) titanium trichloride, bis(cyclopentadienyl) zirconium dichloride, bis(pentamethylcyclopentadienyl) zirconium dichloride, bis(cyclopentadienyl) dimethyl titanium, bis(cyclopentadienyl) diphenyl titanium, pentamethylcyclopentadienyl titanium trichloride, pentaethylcyclopentadienyl titanium trichloride, bis(1,2-dimethylcyclopentadienyl) diphenyl titanium and bis(1,2-diethylcyclopentadienyl) diphenyl titanium.
7. The inorganic / organic composite supported Ziegler-Natta catalyst according to claim 1, characterized in that: The doping amount of the co-catalyst is 10wt% to 20wt% of the Ziegler-Natta catalyst, and the co-catalyst includes alkyl magnesium chloride and aluminoxane; Preferably, the aluminoxane is selected from: methylaluminoxane and / or tetrabutylaluminoxane; Preferably, the alkyl magnesium chloride is selected from one or more of methyl magnesium chloride, ethyl magnesium chloride and butyl magnesium chloride.
8. A method for preparing the inorganic / organic composite support type Ziegler-Natta catalyst according to any one of claims 1 to 7, characterized in that: include: Adding the inorganic / organic composite carrier and alkyl magnesium chloride into a tetrahydrofuran solvent containing alcohol, and stirring to obtain an alcohol adsorption carrier; The metallocene compound and aluminoxane are added to a tetrahydrofuran solvent containing alcohol, mixed with an alcohol adsorption carrier, and stirred to obtain a catalyst carrier; A tetrahydrofuran solvent containing titanium tetrachloride and an alkane solvent are added to the catalyst carrier, and the Ziegler-Natta catalyst is obtained after stirring and drying.
9. The method for preparing the inorganic / organic composite carrier type Ziegler-Natta catalyst according to claim 8, characterized in that: The alcohol is selected from one or more of ethanol, propanol, 1-butanol, ethylene glycol, propylene glycol, and 1,4-butanediol.
10. The method for preparing the inorganic / organic composite carrier type Ziegler-Natta catalyst according to claim 8, characterized in that: The alkane solvent is selected from one or more of n-hexane, isohexane, n-heptane, 2-methylhexane, 3-methylhexane, n-octane, 2-methylheptane and 3-methylheptane.
